Isolated tumor cell clusters (ITC) in lymph nodes and PD-L1 expression on tumor-associated immune cells are prognostic factors for microsatellite instable-high gastric cancers - Menghan Cui; Yangli Zhou; Yin Han; Nannan Chen; Min Zhao; Yan Wang; Fengxia He (Translational Oncology)
Background: Microsatellite instable-high (MSI-H) gastric cancer (GC) represents a distinct subgroup. However, controversy exists regarding the role of MSI in GCs, and the factors leading to internal prognostic differences among MSI-H GCs are rarely studied. Methods: We identified 53 MSI-H cases from 941 consecutive GCs and conducted a detailed investigation of the clinical significance, clinicopathological correlations, and prognostic indicators of MSI-H GCs. Results: Compared to MSI-low (MSI-L)/microsatellite stable (MSS) GCs, the MSI-H cohort was characterized by older age, female predominance, antral location, fewer lymph node (LN) metastases (H&E), and earlier tumor stage, but was also associated with larger tumor size, poor differentiation, and a high incidence of isolated tumor cell clusters (ITC) in negative LNs. ITC was then found to be correlated with tumor volume, Lauren subtype, pT stage, LN status (H&E), and lymphovascular invasion, with tumor size identified as an independent risk factor. Regarding prognosis, MSI-H GCs did not show longer survival time compared to MSI-L/MSS cases overall and in Stage Ⅲ-Ⅳ, but exhibited shorter survival time in Stage Ⅰ-Ⅱ. Moreover, in addition to age, pN stage, and distant metastasis, ITC and PD-L1 expression influenced survival in MSI-H GCs. ITC was confirmed as an independent unfavorable prognostic factor, while PD-L1 expression on interstitial immune cells independently predicted a favorable outcome. Conclusions: Our results suggest that MSI-H GC represents a peculiar clinicopathological entity with frequent occurrence of ITC in negative LNs. ITC and PD-L1 are crucial prognostic indicators for MSI-H patients.